Harari und Ostgurage - Wagner, Ewald (Aethiopica, 2009)
The close relationship between Harari and the East Gurage languages Silṭe, Wolane and Zāy was established already in 1931 by Marcel Cohen, and then confirmed by Wolf Leslau, Robert Hetzron and others. The present article will elaborate this relationship on the basis of the new material on the Eastern Gurage languages presented by Wolf Leslau, Ernst-August Gutt and Ronny Meyer in the last decades. Phonological, lexical, morphological and syntactical phenomena are considered in the course of which special emphasis is laid on the chronology of the separation of the different languages.